SOAL BERPIKIR KREATIF MATEMATIS SISWA SMP BERKONTEKS BENGKULU - Tiara Rezky Dwi Putri; Nyayu Masyita Ariani (Jurnal Math-UMB.EDU, 2019)
ABSTRACTThis research aimed to construct many standardized problems items mathematical creative thinking ability which have Bengkulu contextual. It was held at SMPN 11 Bengkulu city at even semester on academic years 2017/2018. Tessmermodified by Zulkardi was used to developed those problems ones. Tessmer steps was preliminary and formative evaluation. In preliminary prototyping was done, and in formative evaluation developing prossess ware done. 8 of 10 prototype we standardized items, which are valid, practical an difficulty level, power index differences were good or standardized.Â Keywords : creative thinking mathematics, contextual Bengkulu